From hero to antihero and his glory: Elpenor’s Odyssey after the First World War - Costa, Lorena Lopes da (2020)
In 1919, the same year that Jean Giraudoux made his “Adieu Ã  la guerre” [“Farewell to the war”], he wrote “Les morts d'Elpénor” [“The deaths of Elpenor”]. In 1926, alongside three other stories, this text would integrate the book Elpénor [Elpenor], determining this collection of four texts written for eighteen years, the first being “Cyclope” [“Cyclops”], written in 1908; the second “Sirènes” [“Sirens”], in 1912; the third already mentioned in 1919; and the last in 1926, “Les nouvelles morts d'Elpénor” [“The new deaths of Elpenor”]. When “Cyclops” and “Sirens” (with slightly modified titles) were released respectively by Le Matin in 1908 and Paris-Journal in 1912, none of them mentioned Elpenor. In short, it is with the development of the last two stories that Elpenor, this erased character in Homer who is absent in the first Giraudoux's texts as well, steals the spotlight. This article analyzes how the updating of the hero and his stories are in dialogue with the war experienced by the author, thus proposing that old stories, when renewed, participate in a process that allows them to elaborate the challenges of the present, communicating the present through an already known code, which is the Odyssey.